Neo-Aramaic and Kurdish Folklore from Northern Iraq A Comparative Anthology with a Sample of Glossed Texts, Volume 1 - Khan, Geoffrey (Open Book Publishers, 2022)
This comparative anthology showcases the rich and mutually intertwined folklore of three ethno-religious communities from northern Iraq: Aramaic-speaking ('Syriac') Christians, Kurdish Muslims and-to a lesser extent-Aramaic-speaking Jews. The first volume contains several introductory chapters on language, folkore motifs and narrative style, followed by samples of glossed texts in each language variety. The second volume is the anthology proper, presenting folklore narratives in several distinct varieties of North-Eastern Neo-Aramaic and Northern and Central Kurdish. The stories are accompanied by English translations. The material includes different genres such as folktales, legends, fables and anecdotes, and is organised into seven thematic units. The folkloristic material of these three communities is shared to a large extent. The anthology is, therefore, a testament to the intimate and long-standing relations between these three ethno-religious communities-relations that existed in a multilingual environment centuries before the modern era of nationalism.